2016
DOI: 10.1093/hmg/ddw085
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of a human congenital disorder of glycosylation caused by loss of PMM2

Abstract: The most common congenital disorder of glycosylation (CDG), phosphomannomutase 2 (PMM2)-CDG, is caused by mutations in PMM2 that limit availability of mannose precursors required for protein N-glycosylation. The disorder has no therapy and there are no models to test new treatments. We generated compound heterozygous mice with the R137H and F115L mutations in Pmm2 that correspond to the most prevalent alleles found in patients with PMM2-CDG. Many Pmm2R137H/F115L mice died prenatally, while survivors had signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…Importantly, complementation of primary fibroblasts from CDG-0359 with a plasmid containing wild-type SSR3 cDNA completely restored the expression of SSR3 protein and the integrity of the TRAP complex as determined by the reappearance of SSR1 and SSR4 protein levels seen in control fibroblasts (Figure 1). Finally, we show that primary fibroblast from CDG-0359 have abnormal glycosylation of two previously reported marker proteins, GP130 and ICAM1 18,19 (Figure 2). These results along with the abnormal CDT indicate that the mutation in SSR3 compromises N-linked glycosylation.…”
Section: Western Blot Analysissupporting
confidence: 60%
See 1 more Smart Citation
“…Importantly, complementation of primary fibroblasts from CDG-0359 with a plasmid containing wild-type SSR3 cDNA completely restored the expression of SSR3 protein and the integrity of the TRAP complex as determined by the reappearance of SSR1 and SSR4 protein levels seen in control fibroblasts (Figure 1). Finally, we show that primary fibroblast from CDG-0359 have abnormal glycosylation of two previously reported marker proteins, GP130 and ICAM1 18,19 (Figure 2). These results along with the abnormal CDT indicate that the mutation in SSR3 compromises N-linked glycosylation.…”
Section: Western Blot Analysissupporting
confidence: 60%
“…Western blot analysis was carried out as previously described using two commercially available control fibroblast lines GM‐00038, GM‐03348 (Coriell cell repository) and CDG‐0359 to determine the protein levels for SSR1‐4 (Novus Biologicals) . GP130 and ICAM1 western blots were performed as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Schneider and colleagues reported that mannose supplementation rescued the embryonic lethality phenotype in the Pmm2 R137H/F118L model, but Chan and coworkers were unsuccessful in their attempt with the same amount of mannose in Pmm2 R137H/F115L model, which showed 62% embryonic lethality in homozygotes. However, they were able to significantly rescue embryonic lethality in the Pmm2 F115L/F115L homozygous mutants . Nonetheless, Wong and colleagues were able to reverse some of the biochemical phenotypes of PGM1 deficiency in human patients and cells with hypomorphic mutations, despite the fact that not all phenotypes were corrected .…”
Section: Discussionmentioning
confidence: 99%
“…However, they were able to significantly rescue embryonic lethality in the Pmm2 F115L/F115L homozygous mutants. 28 Nonetheless, F I G U R E 5 Abnormal glycosylation of serum transferrin in Pgm2 +/− heterozygotes. Representative transferrin spectra in wild type and heterozygous Pgm2 +/− mice serum evaluated by mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphomannomutase 2 (Pmm2) is involved in the synthesis of the GDP‐mannose and dolichol‐phosphate‐mannose, playing an important role in protein glycosylation. The most common disorder of glycosylation is caused by mutations in Pmm2 that limits availability of mannose precursors required for protein glycosylation . Pyridoxal‐dependent decarboxylase domain‐containing protein (Pdxdc1) is involved in the catalysis of the nonhydrolytic addition or removal of a carboxyl group to or from a compound.…”
Section: Discussionmentioning
confidence: 99%